(untitled) (International Conference on Energy, Intelligence Systems, and Cloud Computing (Ingenio 2026), 2026)
With the rapid growth of renewable energy penetration, grid-forming converters (GFMs) have become essential for the stable operation of new power systems. However, the virtual synchronous generator (VSG) features strong coupling between power and voltage-current control loops due to power electronic multi-timescale dynamics, which easily induces negative damping and low-frequency oscillations (LFOs). Under the commonly adopted constant DC-voltage assumption, the interactions among the active-power and reactive power loops, together with the influence of the fast voltage-current control loops, may still result in insufficient damping and LFO. To solve this issue, this paper proposes a virtual damping control (VDC) strategy for the active power loop. A reduced-order small-signal model considering the coupling between the active-power and reactive-power loops is established, while the voltage-current inner-loop dynamics are neglected under the assumption that they are much faster than the outer-loop dynamics. A VDC scheme employing band-pass filtering and phase compensation is designed to generate supplementary power modulation, providing damping torque to suppress oscillations. Eigenvalue analysis and time-domain simulations validate the proposed method. Compared with traditional virtual impedance (VI) control, the proposed VDC effectively suppresses LFO and improves the damping performance and dynamic stability of the GFM system